Neutrophil Gelatinase‐Associated Lipocalin in Dogs With Sepsis Undergoing Emergency Laparotomy: A Prospective Case–Control Study. (29th September 2015) - Cortellini, S.; Pelligand, L.; Syme, H.; Chang, Y.M.; Adamantos, S.
Abstract : Background: Neutrophil gelatinase‐associated lipocalin (NGAL) is an early indicator of acute kidney injury (AKI) in dogs and its use has not been evaluated in dogs with sepsis. Animals: Fifteen dogs with sepsis requiring laparotomy (study dogs) and 10 dogs undergoing surgery for intervertebral disc disease (control dogs). Objective: To determine whether NGAL increases in dogs with sepsis undergoing emergency laparotomy and whether it is correlated with development of AKI and survival. Methods: Longitudinal study conducted at a referral teaching hospital. Serum neutrophil gelatinase‐associated lipocalin (sNGAL), urinary NGAL normalized to urinary creatinine concentration (UNCR), and serum creatinine concentration were measured at 4 time points (admission, after anesthesia, and 24 and 48 hours postsurgery). Development of AKI (increase in serum creatinine concentration of 0.3 mg/dL) and in‐hospital mortality were recorded. Linear mixed‐model analysis was employed to assess differences between groups over time. Mann–Whitney U ‐test was performed for comparison of continuous variables between groups and Chi square or Fisher's exact tests were used to assess correlation between discrete data. Results: Serum NGAL and UNCR were significantly higher in study dogs across all time points ( P = .007 and P < .001, respectively) compared with controls. Urinary NGAL normalized to creatinine in the study group was not significantly different between survivors (n = 12) and nonsurvivors (n = 3). Dogs that received hydroxyethyl starch had significantly higher UNCR across all time points ( P = .04) than those that did not. Discussion—Conclusion: Serum neutrophil gelatinase‐associated lipocalin and UNCR are increased in dogs with sepsis requiring emergency laparotomy. Additional studies are needed to evaluate its role as a marker of AKI in this population.